2020
DOI: 10.1109/tvcg.2018.2873737
|View full text |Cite
|
Sign up to set email alerts
|

Towards BCI-Based Interfaces for Augmented Reality: Feasibility, Design and Evaluation

Abstract: Brain-Computer Interfaces (BCIs) enable users to interact with computers without any dedicated movement, bringing new hands-free interaction paradigms. In this paper we study the combination of BCI and Augmented Reality (AR). We first tested the feasibility of using BCI in AR settings based on Optical See-Through Head-Mounted Displays (OST-HMDs). Experimental results showed that a BCI and an OST-HMD equipment (EEG headset and Hololens in our case) are well compatible and that small movements of the head can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 27 publications
(53 reference statements)
0
48
1
1
Order By: Relevance
“…When the stimulus duration is less than 3s, AR-Pos2 achieved the highest classification accuracy compared to the other 3 positions, and 89.0% and 94.6% average accuracy could be obtained under the stimulus duration of 2s and 3s. Compared with the existing AR-BCI study [28], this study obtained a higher recognition accuracy by a shorter stimulus duration.…”
Section: B Influence Of Stimulus Duration and Layout On The Classifimentioning
confidence: 63%
See 1 more Smart Citation
“…When the stimulus duration is less than 3s, AR-Pos2 achieved the highest classification accuracy compared to the other 3 positions, and 89.0% and 94.6% average accuracy could be obtained under the stimulus duration of 2s and 3s. Compared with the existing AR-BCI study [28], this study obtained a higher recognition accuracy by a shorter stimulus duration.…”
Section: B Influence Of Stimulus Duration and Layout On The Classifimentioning
confidence: 63%
“…Displaying repetitive visual stimulus via OST-AR technology could overcome the limitations of the vision of PC screen, and improve the portability and flexibility of SSVEP-BCI simultaneously. In 2018, Hakim Si-Mohammed et al verified that it is feasible of combining OST-HMD with BCI through designing and evaluating the application prototype of AR-BCI system [28]. Ming et al designed SSVEP-BCI with OST-AR and achieved 8 commands robotic arm control, their results showed that longer stimulation time is required to guarantee higher accuracy for OST-AR compared with PC screen due to the weakened SSVEP responses evoked by the transparency of stimulation [29].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results were the following: amount of trigger commands necessary to complete the task reduced and amount of errors during the lifting process decreased more than 50% in comparison to the trials when a vision system without AR feedback was utilized. Si-Mohammed et al [109] introduced a BCI system with AR feedback to simplify the control of a mobile robot. Microsoft HoloLens MR goggles were used for visualization of the augmented environment.…”
Section: Ar For Human-robot Interactionmentioning
confidence: 99%
“…Esta misma impresión, sobre el doble papel de los sistemas BCI en videojuegos y entornos de realiad virtual se obtiene de una revisión de 2012 [4] En el campo de la realidad aumentada, se están empezando a publicar estudios ahora. Por ejemplo, el estudio de 2018 [5] realiza un análisis interesante y sistemático sobre la utilización de un sistema BCI basado en SSEVP (potencial evocado de estado estable) con realidad aumentada de 3 comandos para dirigir un robot móvil. Dicho estudio preliminar muestra que un interfaz basado en realidad aumentada con los targets situados en el plano del robot y moviéndose conél, son preferidos por los usuarios debido a que se ahorran la necesidad de hacer operaciones mentales para mapear los signos visuales con la orientación del robot en cada momento.…”
Section: Motivaciónunclassified